PENGGUNAAN MEDIA LEAFLET DENGAN GAME KARPET DALAM MENINGKATKAN PENGETAHUAN KESEHATAN GIGI SISWA/I KELAS V SEKOLAH DASAR NEGERI TANJUNG ANOM - Rawati Siregar; Sri Junita Nainggolan; Aminah Br. Saragih; Kartika Emailijati; Siska Buwana Dhewi (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Dental and oral hygiene is a condition where the teeth in the oral cavity are clean, free from plaque and other dirt on the surface of the teeth such as debris, tartar, and food remains and there is no bad breath. Efforts to increase respondents' knowledge include outreach using carpet media (question cards) and leaflets. The type of research used is quantitative with a quasi-experiment. The sample in this study was all class V, totaling 30 respondents at SDN 104219 Tanjung Anom sub-district with a sampling technique using total sampling. This research uses univariate and bivariate data analysis with the Wilcoxon test and the Man-Whitney test. The statistical test results of this research show that there was a significant difference in increasing knowledge before and after counseling using carpet media (question cards) with a p-value <0.05. There was also a significant difference in the group that used leaflet media between before and after counseling with a p-value <0.05. This research concludes that health promotion using carpet games (question cards) and leaflets is effective in increasing students' knowledge of dental and oral health. It is recommended for dental health workers to develop further research with more research respondents to increase knowledge about maintaining students' oral and dental health.